The effect of sharia compliance and islamic corporate governance on fraud with internal control as moderating variable - Melsiana, Lanvin Fransiska; Kabib, Nur (Islamic Accounting Journal, 2023)
The purpose of this study was to determine the effect of Sharia Compliance (IsIR, PSR, IIR, ZPR, EDR) and Islamic Corporate Governance on Fraud with Internal Control as Moderating Variable in Islamic commercial Bank. The sample used in this study was 13 banks with the sampling technique using purpose sampling. The informated used are 65 annual reports received the documentation method. This study use panel data regression and use moderated regression analysis. The result show that the variable IsIR, ZPR and ICG has a negative and significant effect on Fraud. PSR, IIR and EDR has no effect on Fraud. Internal Control can moderate the effect of ICG on Fraud, but cannot moderate the effect of IsIR, PSR, IIR, ZPR and EDR on fraud.Keywords: sharia compliance, islamic corporate governance, fraud, internal control